Theoretical and experimental study of effects of Co2+ doping on structural and electronic properties of ZnO. (March 2022) - Romeiro, F.C.; Castro, N.S.; Scolfaro, L.; Borges, P.D.; Lima, R.C.
Abstract: In this study, we theoretically investigated the electronic structure of Zn1-x Cox O using different approaches for the exchange-correlation potential comprising GGA with the on-site Coulomb correlation interaction U to the Zn d orbital (GGA +  U Zn ), GGA with modified Becke–Johnson exchange potential (GGA + mBJ), and (GGA + mBJ +  U Zn ). To support the theoretical results, a Co 2+ -doped ZnO sample was obtained experimentally by using the microwave–hydrothermal method. Changes in the structural, vibrational, electronic, and magnetic properties induced by the insertion of the Co 2+ impurities in the ZnO lattice were determined based on first principles calculations. The theoretical results showed that the 3d orbitals derived from Co 2+ appear in the deep region of the band gap. These orbitals are responsible for the magnetic behavior of cobalt doped materials. The energy levels introduced by the Co 2+ dopant ions reduced the theoretical band gap value, which was also observed experimentally. The addition of Co 2+ ions weakened the Raman mode E2H intensity, which was attributed to the increasing distortion induced by doping. Photoluminescence spectroscopy results indicated a reduction in the visible emission region after adding Co 2+ ions, thereby indicating the formation of alternative pathways for the recombination process. Graphical abstract: Theoretical calculations showed Egap decreasing by the 3d orbitals derived from Co 2+ in the deep region of ZnO, which is also observed experimentally. Image 1 Highlights: DFT calculations and experimental analysis of Co 2+ doping in the ZnO lattice. Theoretical magnetism of Zn0.94 Co0.06 O ascribed to 3d orbitals in the ZnO band gap. Disordering of cations around oxygen and local distortions induced by doping. Good agreement between theoretical and experimental Egap values for ZnO and Co 2+ -doped ZnO.